Case report: Cyclosporine A-induced extrapyramidal syndrome following hematopoietic stem cell transplantation - Al-Amrani, Fatema; Al Rawas, Abdulhakeem; Al-Ajmi, Eiman; Al Futaisi, Amna (Frontiers in Neurology, 2023)
1 Introduction: Cyclosporine-A-associated neurotoxicity has been reported in up to 40% of patients. A wide range of neurological adverse effects of cyclosporine have been reported, ranging from mild tremors to fatal leukoencephalopathy. Extrapyramidal (EP) adverse effect is a rare manifestation of cyclosporine neurotoxicity. Cyclosporine-induced extrapyramidal syndrome remains a rare adverse reaction. 2 Design/ Methods: A search for studies in patients from all age groups was performed in databases. We found a total of 10 articles reporting EP as an adverse event for cyclosporine-A. A total of 16 patients were found, and a thorough review of these patients to extract clinical information and lab investigations were performed. Comparison between patients was performed to highlight common clinical presentations, investigations during symptomatic phase and prognosis. We also describe an additional eight-year-old male child who developed cyclosporine-related extrapyramidal signs on day 60 post hematopoietic stem cell transplantation for beta-thalassemia. 3 Conclusion: cyclosporine A can induce neurotoxicity resulting in diverse symptoms. signs of EP are rare manifestations of cyclosporine neurotoxicity and should be considered when evaluating post-transplant recipients of cyclosporine when they present with any EP symptoms. Discontinuation of cyclosporine results in good recovery in most patients.